Further tales of the city when sex was everything...except serious - Maupin, Armistead 1944- (Showtime Networks Inc., 2002)
In the middle of the hippest city in America, the wild residents of 28 Barbary Lane are living the San Francisco high life to the fullest
TV-Miniserie; Drama; Mystery; Romance, 2001-2002
Keywords: Television series; Melodramas; Mystery films; Romance; Liebesfilm; Melodrama; Fernsehserie; Mystery -- Film; Gay men / California / San Francisco / Drama; Single women / California / San Francisco / Drama; San Francisco (Calif.) / Drama; City and town life / California / San Francisco / Fiction; San Francisco (Calif.) / Fiction; Films for the hearing impaired; Television programs; DVDs; Vie urbaine / Californie / San Francisco / Romans, nouvelles, etc; Films pour personnes handicapées auditives; Émissions télévisées; DVD.; television programs; City and town life; Gay men; Single women; California / San Francisco / https://id.oclc.org/worldcat/entity/E39QbtfRDXFGHkw9mhRjjy6DWc; Drama; Fiction; DVD-Video